Legal analysis of the appraisal of evidence based on the rules of sound judgement - Ávila-Pérez, Glenda (2024)
The legal analysis of the evaluation of evidence in the Ecuadorian context focuses on the application of sound criticism on the evidentiary means provided by the parties against the decision adopted by the judges. The main objective of the study is to analyze the lack of normative and doctrinal development regarding the rules of sound criticism, by establishing its clarification and definition to ensure an objective evaluation of evidence in judicial proceedings. In Ruling No. 305-17-sep-cc case No. 1597-16-ep (2017), the Constitutional Court highlighted the importance of applying sound criticism in a consistent and motivated manner, through the support of prudential rules of a legal nature. The case law, in this case, highlights the correct application of the rules of sound criticism by the judges of the Labor Chamber of the National Court of Justice. The judgment illustrates the importance of clearly motivating judicial decisions, ensuring transparency and legitimacy. It concludes that the absence of clear criteria for the implementation of sound criticism in Ecuadorian law highlights the need for legislative revision. The importance of establishing specific parameters to guarantee a well-founded, objective and impartial evaluation of evidence in the judicial sphere is emphasized.